Automaton theory approach for solving modified PNS problems - Imreh, Balázs (Acta Cybernetica, 2002)
In this paper a modified version of the Process Network Synthesis (PNS) problem is studied. By using an automaton theoretical approach, a procedure for finding an optimal solution of this modified PNS problem is presented.